If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -2 = -5x Reorder the terms: -2 + y = -5x Solving -2 + y = -5x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + y = 2 + -5x Combine like terms: -2 + 2 = 0 0 + y = 2 + -5x y = 2 + -5x Simplifying y = 2 + -5x
| 3x/a=b | | (X-5)(x+3)+15=0 | | x^2+61x=60 | | 10p+6r=20 | | N-14=-17 | | 5x^3+45x-20x^2-180=0 | | n*35=16 | | (8-4x)=15 | | 8+6x+x=64 | | 12x+30=18x+18 | | 9c^3-64=0 | | M=2p+3 | | -3d+9=3 | | 9x^2=38x-8 | | 5ln(5x+8)=30 | | -30=-15+b | | -x-8/2 | | t/6-6=15 | | 57y=7(8y-2) | | 6(y+8)-8y=35 | | 1.25*24=30 | | 3/4x=15(4/3) | | -7-1+x=-31 | | 25x*6x+12+16=23*10x | | 9m-22=68 | | 15x(14-2)= | | n*24=30 | | (4/3)3/4x=15(4/3) | | (2y-5)(7y-3)= | | 125-r=68 | | 3x^2+x-6=24 | | 14+3n=-2j+6 |